Metabolic inhibitor screening identifies dihydrofolate reductase as an inducer of the tumor immune escape mediator CD24. Issue 2 (2nd December 2022) - Boese, Austin C.; Hwang, Jung Seok; Young, Isabelle; Malin, Courteney M.; Avalos, Vanessa; Kang, JiHoon; Kang, Sumin
Abstract: Immune checkpoint inhibitors (ICIs) have improved the clinical management of some cancer cases, yet patients still fail to respond to immunotherapy. Dysregulated metabolism is a common feature of many cancers, and metabolites are known to modulate functions in cancer cells. To identify potential metabolic pathways involved in anti‐tumor immune response, we employed a metabolic inhibitor‐based drug screen in human lung cancer cell lines and examined expression changes in a panel of immune regulator genes. Notably, pharmacologic inhibition of dihydrofolate reductase (DHFR) downregulated cancer cell expression of cluster of differentiation 24 (CD24), an anti‐phagocytic surface protein. Genetic modulation of DHFR resulted in decreased CD24 expression, whereas tetrahydrofolate, the product of DHFR, enhanced CD24 expression. DHFR inhibition and the consequent CD24 decrease enhanced T cell‐mediated tumor cell killing, whereas replenishment of DHFR or CD24 partially mitigated the immune‐mediated tumor cell killing that resulted from methotrexate treatment in cancer cells. Moreover, publicly available clinical data analyses further revealed the link between DHFR, CD24, and the antitumor immune response in lung cancer patients. Our study highlights a novel connection between folate metabolism and the anti‐tumor immune response and partially interprets how DHFR inhibitors lead to clinical benefits when combined with cancer immunotherapy agents.